Safeguarding what and for whom? The role of institutional fit in shaping REDD+ in Mexico - McDermott, C; Ituarte-Lima, C (Resilience Alliance, 2016)
This paper examines the UN Framework Convention on Climate Change mechanism Reducing Emissions from Deforestation and Degradation (REDD+), and its associated multitude of global to local safeguards, as they apply to a single ejido on the Yucatan Peninsula, Mexico. It draws on written sources and interviews to analyze the ways in which broad international norms articulated through the REDD+ safeguards, including support for human rights and sustainable livelihoods for local communities, are translated at national, regional, and local levels. Our findings indicate a wide range of perspectives on what constitutes sustainability, from strict conservation to more forest use-oriented strategies, such as community forestry and traditional Mayan shifting cultivation. These visions, in turn, shape what types of REDD+ interventions are considered a good “environmental fit,” i.e., that fit the environmental problems they aim to address. Fits and misfits also occur between institutions, and play a core role in determining whose visions of sustainability prevail. We found a good fit in the case study ejido between REDD+ and the Payment for Ecosystem service (PES) scheme, which sets the parameters for what counts as “sustainable livelihoods” within a strict conservation paradigm. We likewise found a good fit between REDD+ safeguards and institutions supporting local community rights to reject REDD+ projects. However, despite the strength of procedural safeguards, the parameters of the PES scheme constrained the choice of REDD+ activities available, including the possibilities of local people to work on the farm and in the forest, and hence the scope of its distributive benefits. This highlights the important, but also problematic, roles of institutional and environmental “fit” in determining whose rights are safeguarded and what is recognized as a sustainable livelihood strategy. It also calls for more proactive efforts to expand the range of REDD+ activities in ways that safeguard livelihood diversity.